A Analysis of Tempering Treatment after Hardening on S45C steel Bogie Pin Materials in relation to Mechanical Strength - Wibowo, Heri; Marwanto, Arif; Kusdiyarto, Prihatno; Prasetio, Mukhamad Andri (Journal of Engineering and Applied Technology, 2025)
S45C steel is a medium carbon steel used for railway bogie pins due to its high strength. However, this steel does not meet the minimum hardness standard for bogie pin products, requiring further processing. The specific objectives of this study are: a) to investigate the effect of tempering temperature variations on the mechanical properties of S45C steel, and b) to determine the optimal tempering temperature and time recommended for heat treatment of S45C steel. The research method applied was an experiment with hardening treatment at a temperature of 910°C for 20 minutes, followed by tempering treatment at temperatures of 175°C, 225°C, and 275°C for 20 minutes of air cooling. The testing process carried out included tensile strength testing, hardness testing, and microstructure testing. The results of this study showed that the test specimen with tempering treatment at a temperature of 175℃ was the best among the other test specimens because it was more suitable for industrial needs. This test specimen had a maximum stress value of 948.6 MPa, a maximum strain value of 7.76%, a Vickers hardness value of 358.06 VHN, and a microstructure consisting of ferrite and martensite phases, making the tempering process at a temperature of 175℃ almost close to the standards set by the company.